Comparative study for effects of chemical mutagenesis on seed germination, survivability and pollen sterility in M1 and M2 generations of Dianthus - Roychowdhury, Rajib; Alam, Molla Jaunatul Ferdousul; Bishnu, Sunanda; Dalal, Tinkari; Tah, Jagatpati (Plant Breeding and Seed Science, 2012)
Chemical mutagenesis is an efficient tool used in mutation breeding programme for improving various vital characteristics in floricultural crop, like Dianthus. In this study, ethyl methane sulphonate (EMS), sodium azide (SA) and colchicine (COL) with three different concentrations (0.1%, 0.4% and 0.7%) were used to analyse their effect on seed germination behaviour, survivability and pollen sterility in both first (M1) and second (M2) mutant generations. It was noted that increase in the dose of EMS and SA, germination percentage and survivability were decreased; whereas colchicine doses were proportional to increase germination percentage at seedling stage, but they were not survived till maturity. In M1 and M2, higher lethality over control (44.3 and 32.89, respectively) was shown by 0.7% of SA and EMS, respectively. Pollen sterility was also increased with increasing mutagenic doses. The maximum pollen sterility was 71.8% and 61.1% for 0.7% COL in M1 and M2, respectively. So, the effect of chemical mutagenesis on biological parameters with SA (0.7%) treatment in M1 and EMS (0.7%) treatment in M2 were much more beneficial as compared to colchicine. For each studied parameter, chemical mutagenesis was higher in M1 than M2. Hence, for the first time in Dianthus, we reported that these mutagens can be used for improving the germination behaviour and the metrical traits in Dianthus cultivar.